The impact of obesity and adipokines on breast and gynecologic malignancies. Issue 1 (27th October 2022) - Tewari, Surabhi; Vargas, Roberto; Reizes, Ofer
Abstract: The link between obesity and multiple disease comorbidities is well established. In 2003, Calle and colleagues presented the relationship between obesity and several cancer types, including breast, ovarian, and endometrial malignancies. Nearly, 20% of cancer‐related deaths in females can be accounted for by obesity. Identifying obesity as a risk factor for cancer led to a focus on the role of fat‐secreted cytokines, known as adipokines, on carcinogenesis and tumor progression. Early studies indicated that the adipokine leptin increases cell proliferation, invasion, and inhibition of apoptosis in multiple cancer types. As a greater appreciation of the obesity–cancer link has amassed, we now know that additional adipokines can impact tumorigenesis. A deeper understanding of the adipokine‐activated signaling in cancer may identify new treatment strategies irrespective of obesity. Moreover, adipokines may serve as disease biomarkers, harnessing the potential of obesity‐associated factors to serve as indicators of treatment response and disease prognosis. As studies investigating obesity and women's cancers continue to expand, it has become evident that breast, ovarian, and uterine cancers are distinctly impacted by adipokines. While complex, these distinct interactions may provide insight into cancer progression in these organs and new opportunities for targeted therapies. This review aims to organize and present the literature from the last 5 years investigating the mechanisms and implications of adipokine signaling in breast, endometrial, and ovarian cancers with a special focus on leptin and adiponectin. Abstract : There is evidence for a link between obesity and breast, ovarian, and endometrial cancers. Fat‐secreted cytokines, known as adipokines, impact carcinogenesis and tumor progression. Understanding adipokine activated signaling in cancer may provide insight into new treatments, biomarkers, and disease progression. This review presents the literature investigating the mechanisms and implications of adipokine signaling in breast, endometrial, and ovarian cancers with a special focus on leptin and adiponectin.